KUANTITAS DAN KUALITAS BUAH SALAK GULAPASIR DI BEBERAPA SENTRA PRODUKSI DI BALI - Gidion Lobo Lenga; I Ketut Sumantra; Farida Hanum; I Ketut Widnyana (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2022)
This study aims to determine the quantity and quality of salacca (salak) Gulapasir in several production centers in Bali. The method used is the survey method for production. For the quality of fruit, use Complete Randomized Design (CRD) with four replicates, while for Vitamin C levels, total acid and TSS were repeated three times. Planting location as a treatment consists of salak from Karangasem, Badung, Tabanan, Bangli, and Gianyar districts. Variable observed research is fruit weight per bunch and per seed, total fruit, the thickness of meat fruit, vitamin C content, total acid, and total solids dissolved (TSS). The results of the study show that produce fruit from Karangasem Regency shows the highest production in two seasons (between season 1 and Gadu) with a total production of 6 kg/tree. Salak Gulapasir comes from the districts of Karangasem, Badung, Tabanan, Bangli and Gianyar have different qualities. Salak Gulapasir harvested in Karangasem Regency shows weight, quantity, and thickness highest and different from districts Gianyar. Snake fruit Sugar from Karangasem gives the highest and different content of vitamin C, TSS, and total acid with salak from Gianyar. Plant location no show difference to shelf life. Shelf life salak Gulapasir range between 4.75-7.75 days, with a shelf life shortest, happens to the salak from Bangli